Commanding language: Linguistic authority and female autonomy in Thomas Hardy's fiction. - Malton, Sara. (University of Ottawa (Canada), 2000)
This thesis examines the fluid relationship between linguistic control and female autonomy and power in four novels by Thomas Hardy. Chapter One attends to the way in which the constructive use of dialogue in Far From the Madding Crowd (1874) enables Bathsheba Everdene's integration into generative social, economic, and personal relationships. Chapter Two examines The Return of the Native (1878), focusing on gossip's role in Eustacia Vye's destruction, which is the consequence of her defiance of public discourse. Chapter Three explores A Laodicean (1881), centering on Hardy's depiction of Paula Power's control of language, which is facilitated by her access to property, wealth, and communication technologies. Chapter Four addresses Jude the Obscure (1895), particularly the portrayal of Sue Bridehead, whose demise results from her unorthodox challenge to the way patriarchal texts circumscribe human relationships and identity.
Keywords: Literature, English.